2015
DOI: 10.5812/ijpbs.229
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Cannabinoids, and Opioids Abuse and Dependence Among Psychiatric Inpatients

Abstract: Background: While substance abuse among psychiatric patients is a widely known problem in clinical practice, there is no local study about prevalence and co-occurrence of substance abuse in north of Iran. Objectives: The present study was designed to determine the frequency of smoking, alcohol, opioid and cannabinoid substances, and prescription medicines abuse or dependence among Psychiatric Inpatients. Patients and Methods: A cross-sectional 2-year case register study was conducted on all (n = 492) psychiatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The study suggests that patients like to quit smoking but they need help to do so, due to the fact that they cannot quit by themselves. Other studies show that most of the patients agreed that it is too hard for them quit smoking, and a smoking room is not a good choice for them because these rooms will make it difficult for them to quit smoking [ 8 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study suggests that patients like to quit smoking but they need help to do so, due to the fact that they cannot quit by themselves. Other studies show that most of the patients agreed that it is too hard for them quit smoking, and a smoking room is not a good choice for them because these rooms will make it difficult for them to quit smoking [ 8 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although people with mental illness are about twice as likely to smoke as other persons [ 7 ], Iranian studies showed that smoking rate was approximately three times higher in psychiatric patients than what has been reported from the general population [ 8 ].…”
Section: Introductionmentioning
confidence: 99%